Composition & Ecological Role of Soil Macrofauna in Selorejo and Punten Citrus Farming, Malang - East Java - Fitria Karinasari; Zulfaidah Penata Gama; Amin Setyo Leksono (Biotropika: Journal of Tropical Biology, 2021)
Conventional citrus crop farming is a citrus farming system that uses citruscultivation techniques with maximum use of chemicals material to support asustainable agricultural system. Indicators of environmental quality can be known from the composition and ecological role of fauna, one of which is soil macrofauna. This research aims to investigate the diversity and community structure of the soil macrofauna and to identify its role in citrus farming at Selorejo, Dau and Punten Villages, Bumiaji, Malang Regency. This study is a descriptive exploratory study in order to study soil macrofauna capturing at each location for three times. The observation method of soil macrofauna used pitfall traps and hand shorting methods. All data were tabulated used Microsoft Excel. Abiotic factor measurements for two locations have a no different value in each sampling plot. The composition of soil macrofauna is obtained from the important value index (IVI) and the Shannon-Wiener diversity index (H'). Soil macrofauna was obtained from two locations as many as 21 families with the highest importance value index (IVI), namely Formicidae. The results showed that Selorejo citrus farming consists of predator 46%, herbivorous 25%, decomposer 11%, scavenger 7%, and others 11%, while in Punten citrus farming consists of 55% predator, 10%herbivorous,15% decomposer,5% scavenger, and others 15%